Racial differences in inequality aversion: Evidence from real world respondents in the ultimatum game - John Griffin; David Nickerson; Abigail Wozniak (Institute for the Study of Labor (IZA), 2011)
The distinct historical and cultural experiences of American blacks and whites may influence whether members of those groups perceive a particular exchange as fair. We investigate racial differences in fairness standards using preferences for equal treatment in the ultimatum game, where responders choose to allow a proposed division of a monetary amount or to block it. Although previous research has studied group differences in the ultimatum game, no study has been able to examine these across races in America. We use a sample of over 1600 blacks and whites drawn from the universe of registered voters in three states and merged with information on neighborhood income and racial composition. We experimentally vary proposed divisions as well as the implied race of the ultimatum game proposer. We find no overall racial differences in acceptance rates or aversion to inequality. However, we uncover racial differences in ultimatum game behavior on other dimensions. Many of these are driven by the lowest income group in our sample, which represents the 10th percentile of the black income distribution. We also find that blacks are more sensitive to unfair proposals from other blacks.
urn:nbn:de:101:1-201104133915
Keywords: J15; D03; D63; C72; C91; 330; racial differences; inequality aversion; ultimatum game; artefactual experiments; Farbige Bevölkerung; Ethnische Gruppe; Gerechtigkeit; Ultimatumspiel; Test; USA